2021
DOI: 10.1155/2021/5554837
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, Characterization, and Impact of Heat Treatment on Sliding Wear Behaviour of Aluminium Metal Matrix Composites Reinforced with B4C

Abstract: The aim of this research paper is to find the wear behaviour of Al7075 MMCs. In this investigation, the wear tests on the as-cast and age-hardened specimens were performed on an advanced rotary tribometer. The materials selected for the analysis are Al7075 as a matrix, and the reinforcements are boron carbide. By using stir casting, metal matrix composites are manufactured by adding B4C as a reinforcement particulate in Al7075. The fabricated composites were characterized and the wear behaviour of these compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Particulate Reinforcement Used to Synthesis HAMCs. The cost of the particulate reinforced composites (SiC, Al 2 O 3 , and Gr) is less than the fiber-reinforced composites, due to the lower cost of particles [25]. Moreover, the physicomechanical, tribological, and corrosion properties of particulates are generally isotropic.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Particulate Reinforcement Used to Synthesis HAMCs. The cost of the particulate reinforced composites (SiC, Al 2 O 3 , and Gr) is less than the fiber-reinforced composites, due to the lower cost of particles [25]. Moreover, the physicomechanical, tribological, and corrosion properties of particulates are generally isotropic.…”
Section: Methodsmentioning
confidence: 99%
“…The physicomechanical characteristics of Al, SiC, Al 2 O 3 , Gr, and SCBA reinforced MMCs are superior to those of the base metal (pure Al) and its alloys [24,25]. The general physicomechanical properties of Al, SiC, Al 2 O 3 , Gr, and SCBA are depicted in Table 3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of the particulate-reinforced composites (SiC, Al 2 O 3 , and Gr) is less than the fiber-reinforced composites, due to the lower cost of particles [44]. Moreover, the physicomechanical, tribological, and corrosion properties of particulates are generally isotropic.…”
Section: Particulate Reinforcements Utilized In the Fabrication Of Hamcsmentioning
confidence: 99%
“…For applications in the automotive and aerospace industries, lightweight and high-performance materials are required. The lightweight material is produced by developing composites with hard reinforcement particulates in the matrix of soft material [7]. Singh et al reported that, for application in the automobile, aerospace, and aircraft industries, lightweight and high-performance materials are required [7].…”
Section: Introductionmentioning
confidence: 99%